1987
DOI: 10.1111/j.1432-0436.1987.tb01553.x
|View full text |Cite
|
Sign up to set email alerts
|

Retention of lens specificity in long-term cultures of diploid rabbit lens epithelial cells

Abstract: Abstract. Rabbit lens epithelial cells from newborn animals exhibited limited growth when cultured under standard conditions. Cell lines were generated when explants from individual lenses were cultured in medium supplemented with conditioned medium or untreated rabbit serum. All lines exhibited a stable epithelial morphology. One line, N/ N1003A. was examined extensively with respect to its growth, ploidy, and maintenance of lens‐specific functions. Cells at population‐doubling level (pdl) 120 exhibited a no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0

Year Published

1998
1998
2007
2007

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 23 publications
(35 citation statements)
references
References 33 publications
0
35
0
Order By: Relevance
“…The rabbit lens epithelial cells (RLECs), N/ N1003A, was a gift from Dr John Reddan [55]. N/N1003A cells were grown in Eagle's minimal essential medium (MEM; Sigma M0643) containing 10% rabbit serum (Sigma R4505).…”
Section: Methodsmentioning
confidence: 99%
“…The rabbit lens epithelial cells (RLECs), N/ N1003A, was a gift from Dr John Reddan [55]. N/N1003A cells were grown in Eagle's minimal essential medium (MEM; Sigma M0643) containing 10% rabbit serum (Sigma R4505).…”
Section: Methodsmentioning
confidence: 99%
“…Previous in situ hybridization studies showed that MafB mRNA was present in the embryonic lens (8,46). Expression of MafB in the adult lens was determined by Western immunoblotting of extracts obtained from microdissected adult lens fiber cells, lens epithelial cells, and extracts of two lens-derived cell lines, ␣TN4-1 (43) and N/N 1003A (42). MafB protein was detected in microdissected lens epithelial cells as well as in the established lens epithelial cell lines, but not in the fiber cells ( Fig.…”
Section: Pl1 and Pl2 Elements Are Essential For Chicken ␤B1-crys-mentioning
confidence: 99%
“…Cell Culture and Transfection-N/N 1003A cells (a rabbit lens epithelium derived cell line) (42) were transfected following the LipofectAMINE Plus reagent protocol provided by Invitrogen. Generally 6 ϫ 10 5 cells were plated for each 60-mm dish at least 8 h before transfection, each dish received 2.5 g of promoter/chloramphenicol acetyltransferase (CAT) plasmid, 0.5 g of pCMV/␤GAL, and 0.5 g of various expression plasmids.…”
Section: Rt-pcr Analysis Of C-maf Isoform Expression Inmentioning
confidence: 99%
“…RLECs, N/N1003A (a kind gift from Dr John Reddan) (Reddan et al, 1986), were grown in Eagle's minimum essential medium containing 10% rabbit serum as described previously (Mao et al, 2001). The medium was prepared in ion-exchanged double-distilled water to give an osmolarity of 30075 mosmol supplemented with 26 mM NaHCO 3 and 50 mg/ ml gentamycin sulfate.…”
Section: Cell Culturementioning
confidence: 99%